Immune reconstitution inflammatory syndrome‐associated lymphoma: A retrospective Brazilian cohort - Juliano Cordova Vargas; Karin Zattar Cecyn; Mariana deOliveira Marques; Juliana Pereira; Walter M. Tobias Braga; Nelson Hamerschlak; Jacques Tabacof; Caina D. deLiz; André Abdo; Paulo Roberto Abrão Ferreira; Gisele W. Braga Colleoni; Otavio C. G. Baiocchi (eJHaem, 2024)
Abstract After initiating combined antiretroviral therapy (cART), individuals with human immunodeficiency virus (HIV) may develop Hodgkin/non‐Hodgkin lymphoma due to immune reconstitution inflammatory syndrome (IRIS). This retrospective cohort study evaluated the incidence, clinical features and prognosis of IRIS‐associated lymphomas in Brazilian patients. Incidence in 2000–2019 was 9.8% (27/276 patients with HIV and lymphoma; viral load drop >1 log). Time between HIV diagnosis and cART initiation was <1 year in 70.3% of cases. Time between cART initiation and lymphoma diagnosis was <3 months in 11 cases and 3–6 months in 16 cases. Overall and progression‐free survival rates were similar between cases of non‐IRIS‐associated lymphoma and IRIS‐associated lymphoma.